The Influence of Biologically Synthesized Copper Nanoparticles on the Biofilm Produced by Staphylococcus haemolyticus 1solated from Seminal Fluid - Romi, Zahraa Mahmoud; Ahmed, Mais Emad (Iraqi Journal of Science, 2024)
Staphylococcus haemolyticus is one of the most frequently isolated coagulase-negative staphylococci. The ability to form biofilm is considered as one of the most important virulence factors of coagulase negative staphylococci. There is only limited knowledge of the nature of S. haemolyticus biofilms. This study was aimed at evaluating the ability of S. haemolyticus strains to produce biofilm in the presence of copper oxide nanoparticles (CuONPs). The biological synthesis of nanoparticles is an environmentally friendly approach for large-scale production of nanoparticles. Copper oxide nanoparticles were produced in the current study from the S. haemolyticus viable cell filtrate. UV-visible (UV-Vis) spectroscopy, X-ray diffraction (XRD), atomic force microscope (AFM), field emission scanning electron microscope (FE-SEM), energy-dispersive X-ray spectroscopy (EDX) and zeta potential (ZP) analysis were used to analyze the newly synthesized CuONPs. Our findings revealed that at minimum inhibitory concentration (MIC), CuONPs showed remarkable inhibition on the biofilms produced by multidrug resistant (MDR) S. haemolyticus isolates.